An in-vivo study on anti-emetic and in-vitro study on anthelmintic properties of cassia fistula - Adrita, Tasnuva Shahreen (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.